Sustainable production and dissemination of genetically improved farmed tilapia seed in smallholder farming systems: A case study from Timor-Leste - Pant, Jharendu; Bhujel, Ram C.; Du Carmu, Adriano; De Jesus, Lucas Soares; Gomes, Silvino; Pereira, Mario; Teoh, Shwu Jiau (Elsevier Masson, 2024)
CONTEXT: Timor-Leste's National Aquaculture Development Strategy (NADS) 2012–30 aims to achieve an annual aquaculture production of 12,000 tons by 2030 to raise per capita fish consumption from 6.1 kg in 2010 to 15 kg. Genetically Improved Farmed Tilapia (GIFT) is identified as the most suitable species under Timor-Leste's existing farming systems and agro-ecological context. It is expected to account for two-thirds of total aquaculture production, requiring over 30 million fingerlings annually, necessitating a strong role of public and private sectors to develop a sustainable hatchery model for producing and supplying high quality GIFT fingerlings to fish farmers on a mass-scale. OBJECTIVE: The major objective was to conceptualize and apply a public-private partnership (PPP) model to produce and disseminate high-quality monosex GIFT seed by public and private hatcheries across Timor-Leste. METHODS: Model GIFT hatcheries were established and monitored using a standard protocol developed by the R&D team. Data on total eggs, clutch size, incubation survival rate, swim-up fry, and monosex fry produced were recorded on a weekly basis. The performance of hatcheries was compared using descriptive statistics at a 5% level of significance. Economic analysis was conducted to compare production costs, gross profits, and net profits among hatcheries and nurseries. Enabling conditions and factors for effective PPP were identified. RESULTS AND CONCLUSIONS: The WorldFish, in collaboration with Timor-Leste's Ministry of Agriculture and Fisheries, upgraded an existing public hatchery in Gleno, Ermera, introduced GIFT in 2015, and developed it as a GIFT broodstock centre to supply quality brood fry to other hatcheries. To produce monosex seed on a mass-scale, four PPP model GIFT hatcheries were established between 2019 and 2023. Results from a public hatchery and two initially established PPP model hatcheries showed that the hatchery in Parlamento had significantly higher (P < 0.05) monthly production of eggs, swim-up fry, monosex fry, and clutch sizes. On average, over 177,000 monosex fry per month were produced by those three hatcheries. Local service providers (LSPs), self-employed youths who have been recruited and trained to facilitate input supply and output marketing, purchase GIFT fry from the hatcheries, nurse them to fingerling size, and supply them to farmers. To achieve high seed production and supply targets, scaling of PPP model hatcheries, nurseries, and LSPs along with effective training and technical back-up, favourable policies, institutional environments, and governance mechanisms, is necessary. SIGNIFICANCE: The PPP model GIFT hatcheries are scalable across inland farming systems in Timor-Leste and other countries with similar agro-ecological, socio-economic, and climatic contexts.